Designs of PMSMs with Inner and Outer Rotors for Electric Bicycle Applications - Taha, Harwan Mohammed; Alnaab, Ismaeil (Kurdistan Journal of Applied Research, 2019)
In this paper, designs of two rotor structures of permanent magnet synchronous motor (PMSM) are proposed in order to find the suitable one to drive an electric bicycle, namely, inner rotor and outer rotor. Both motors are designed to run at a rated speed of 20 Km/h and rated power of 250 W. This paper compares the performance of both proposed motors and the comparison between them is in terms of motor size, weight, cost and efficiency. In addition, this work uses the second design, which is the PMSM with outer rotor to investigate the effects of some motor parameters on motor performance; the parameters are current, advanced angle, stack length and external diameter. In this work, Motor Solve software is used to design and analyze the performance of both motors. According to the simulation and calculation results, both motors achieved the required rated speed and torque at high efficiency and reasonable cost. Nevertheless, the PMSM with inner rotor obtained the required specifications with lighter weight and smaller size than the PMSM with outer rotor. Therefore, it is a proper choice for driving an electric bicycle that has a limitation regarding the motor space. Regarding parameters’ effect, the simulation figures and data show that the motor torque will increase if we increase supply current, stack length and external diameter, while speed decreases as it inversely changes with torque. Except for advance angle which helps motor to produce maximum possible torque at a higher speed.